Comparing Reforms of Juvenile Justice in Bangladesh and Malaysia - Nahid Ferdousi (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2020)
The article attempts to critically compare juvenile justice reforms in both jurisdictions of Bangladesh and Malaysia. It explores legal reforms in line with the international standards to ensure the effective juvenile justice system as well as child well-being in the respective legal systems. The juvenile justice practice of Bangladesh and Malaysia are a testament that diverse juvenile laws, norms and systems exist. After ratification of UNCRC, significant progress has been achieved in both countries. Malaysia adopted mechanisms for rehabilitation in terms of job-based education and alternatives measures by the Child Act 2001. Child-oriented justice and alternative measures have started with the commencement of Children Act 2013 in Bangladesh. For both countries, there is a need for establishing a child-friendly justice system, which would ensure sustainable juvenile justice.